Methods for studying the ecology of soil micro-organisms - Parkison, D. (ed.).; Gray, T.R.G.; Wolloams, S.T. (Oxford Blackwell Scientific Publications [for the] International Biological Programme, 1971)
IBP Handbook; No. 19
Keywords: Soil microbial ecology